'Whose agenda? Who knows best? Whose voice?' Co-creating a technology research roadmap with autism stakeholders. Issue 2 (7th February 2020) - Parsons, Sarah; Yuill, Nicola; Good, Judith; Brosnan, Mark
Abstract: Technologies play vital roles in the learning and participation of autistic people and yet have mostly been conceptualised according to a medical model of disability. In this stakeholder review, the comments of 240 participants from a two-year seminar series focusing on autism and technology were analysed to co-construct an understanding of how research could develop more inclusively. Our socio-cultural analysis shows that stakeholders were very positive about the roles that technologies can play in many areas of life, but that these technologies need to be developed and evaluated according to the needs and preferences of autistic people and their families. We propose an inclusive common social framework for research based on the core themes of social inclusion, perspectives, and participation and agency. Such a framework requires the field to recognise that some current practices are exclusionary and that a commitment to action is needed in order to make positive changes.